2012
DOI: 10.1089/jmf.2011.2105
|View full text |Cite
|
Sign up to set email alerts
|

Cordyceps militaris Extract Attenuates D-Galactose-Induced Memory Impairment in Mice

Abstract: Memory impairment is one of main clinical symptoms of brain senescence. To address the effects of Cordyceps militaris Link extract (CE) on memory impairment, a D-galactose (D-Gal)-induced aging mouse model was employed. Mice injected with D-Gal showed a significant learning and memory impairment that was rescued by CE treatment. The mechanism was further investigated by analyzing the protein level and activity of oxidant and antioxidant molecules, including malondialdehyde (MDA), monoamine oxidase (MAO), total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Long-term D-galactose injection induces changes that resemble natural aging in experimental animals, such as cognitive dysfunction, oxidative damage, and cholinergic dysfunction (Li et al 2012;Xian et al 2014). In this study we observed that, administration of D-galactose to mice caused cognitive deficit and showed deterioration of learning and memory capacity when Morris water maze was applied.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Long-term D-galactose injection induces changes that resemble natural aging in experimental animals, such as cognitive dysfunction, oxidative damage, and cholinergic dysfunction (Li et al 2012;Xian et al 2014). In this study we observed that, administration of D-galactose to mice caused cognitive deficit and showed deterioration of learning and memory capacity when Morris water maze was applied.…”
Section: Discussionmentioning
confidence: 61%
“…One of the mechanisms that has been put forward is that, longterm administration of D-galactose enhances the formation of free radicals which attack lipids and proteins, produces several byproducts and also leads to decrement of antioxidant enzyme activities (Kumar et al 2011;Li et al 2012). According to the free radical theory of aging, free radicals play role in mediating accelerating aging and neurodegeneration (Harman 1956).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) act by scavenging the superoxide anion and H 2 O 2 to prevent reactiveoxygen-species-(ROS-) induced damage [13]. D-galactose (D-gal) induced oxidative stress test was often used to selected medicine with anti-oxidative stress and anti-aging activity [14][15][16][17]. The results exhibited that administration of D-gal 300 g/kg daily for 8 weeks prior to training induced a significant increase in memory injury, oxidative stress was also induced by D-gal.…”
Section: Discussionmentioning
confidence: 99%
“…We check that the quantity of oxidative hits to DNA per cell daily is around 100,000 inside the model rodents and around 10,000 inside the human. DNA-fix synthetics capably dispense with most, yet not all, of the wounds outlined [6,[29][30][31] for instance, the significant change repeat in human lymphocytes, of which the responsibility of oxidative DNA bruises is dark, is around numerous occasions more vital in elderly people than in youths [32]. Mitochondrial DNA (mtDNA) from rat liver has in more than numerous occasions the level of oxidative DNA hurt than does nuclear DNA from an indistinguishable tissue [16,33].…”
Section: Oxidative Stress and Damage To Nucleic Acid Protein And Lipidsmentioning
confidence: 99%